A Systematic Review on Investment Risks in Hydropower to Developing Sustainable Renewable Energy Systems - Adhikari, Sagar; Sopin, Jirakiattikul; Techato , Kua-Anan; Mudbhari, Bibek Kumar (International Journal of Energy Economics and Policy, 2023)
Hydropower is regarded as one of the most important renewable energy sources for the present and the future. However, hydropower projects are exposed to various risks and uncertainties, including economic, environmental, social, geological, regulatory, political, technological, financial, climate, natural, and safety concerns. Thus, to know the existing risks in the hydropower sector, a systematic literature review is conducted to find all peer-reviewed articles in English published between 2018 and 2022 that dealt with investment risks and uncertainties associated with hydropower. This systematic review paper considers 'Hydropower Investment Risk' critical to developing sustainable renewable energy systems. The keywords selected for the search are tailored to identify all the relevant articles related to 'Investment Risk in Hydropower,' where hydropower is referred to as mini, micro, and large hydropower. In addition, the keywords that correspond to investment risk in the hydropower sector are chosen. Two crucial databases 'Scopus' and 'Google Scholar' search yielded 6689 and 123,000 articles, respectively. Among 34 full texts, 31 primary source articles and 3 secondary source articles are reviewed. The many investment risks pertaining to hydropower investments obtained from the extensive review are: 1. risks related to climate change and hydrology 2. Risks related to environment and anthropogenic 3. Market risks related to credit, capital, and other financial risks 4. Risks related to substitution from renewable energy to fossil fuels 5. Risks related to socio-political and technological changes 6. Risks related to institution, policy, legality, and regulatory 7. Risks related to human capital development, and 8. Impact of climate change on hydropower's revenue generation.